A most noble heir - Mason, Susan Anne (Bethany House, a division of Baker Publishing Group, 2018)
"When stable hand Nolan Price learns from his dying mother that he is actually the son of the Earl of Stainsby, his plans for a future with kitchen maid Hannah Burnham are shattered. Once he is officially acknowledged as the earl's heir, Nolan will be forbidden to marry beneath his station. Unwilling to give up the girl he loves, he devises a plan to elope--believing that once their marriage is sanctioned by God, Lord Stainsby will be forced to accept their union. However, as Nolan struggles to learn the ways of the aristocracy, he finds himself caught between pleasing Hannah and living up to his father's demanding expectations. At every turn, forces work to keep the couple apart, and a solution to remain together seems further and further away. With Nolan's new life pulling him irrevocably away from the woman he loves, it seems only a miracle will bring them back together."--Page 4 of cover.